Comparison of anterior transthoracic debridement and fusion with posterior transpedicular debridement and fusion in the treatment of mid-thoracic spinal tuberculosis in adults - Weiwei Li (BMC Musculoskeletal Disorders, 2019)
Abstract Background The surgical procedures for mid-thoracic spinal tuberculosis mainly include anterior transthoracic debridement and fusion and posterior transpedicular debridement and fusion. Until now, the surgical choice is still controversial. This study aims to compare the clinical efficacy of anterior transthoracic debridement and fusion with posterior transpedicular debridement and fusion in the treatment of mid-thoracic (T5–9) spinal tuberculosis in adult patients. Methods Eighty-seven cases with mid-thoracic spinal tuberculosis were treated with anterior transthoracic debridement and fusion (Group A, n = 39) and posterior transpedicular debridement and fusion (Group B, n = 48) from January 2007 to June 2014. Parameters including the operation time, blood loss, time of ESR and CRP decreasing to the normal level, time of abscess disappearance, time of bone graft fusion, rate of surgical complications, Visual Analog Scale (VAS) score, kyphosis angle and SF-36 scale were compared between two groups to evaluate their therapeutic effects. Results All patients were followed up for 5–10 years with the mean of 6.2 ± 1.1 years. No significant differences were observed regarding the gender composition ratio, age, course of disease, number of lesion segments, and preoperative indexes of ESR, CRP, VAS score, kyphosis angle and SF-36 scale between the two groups. Besides, no significant differences were observed regarding VAS score, kyphosis angle and SF-36 scale between the two groups in the 5th postoperative year (P > 0.05). However, the operation time (158.2 ± 10.7 min vs. 183.7 ± 14.1 min), blood loss (517.9 ± 76.5 ml vs.714.6 ± 57.4 ml), time of ESR (2.3 ± 1.1 months vs.3.1 ± 1.4 months) and CRP (1.1 ± 0.3 months vs.1.2 ± 0.6 months) decreasing to the normal level, time of abscess disappearance (2.7 ± 1.6 months vs.4.9 ± 1.9 months), and time of bone graft fusion (6.6 ± 0.8 months vs.8.0 ± 9.6 months) in Group A were less than those in Group B (P < 0.05). Conclusions Both anterior transthoracic debridement and fusion and posterior transpedicular debridement and fusion have a low risk of surgical complications and provide good quality of life for the patients with mid-thoracic (T5–9) spinal tuberculosis followed up in the mid-term. Moreover, the anterior procedure leads to early resolution of the disease and faster fusion.